Household food insecurity is independently associated with poor utilization of maternal healthcare services in Bangladesh - Ghose Bishwajit; Sanni Yaya (Canadian Science Publishing, 2017)
Introduction: Food insecurity at the individual level has been shown to be associated with the adoption of risky behavior and poor healthcare-seeking behavior. However, the impact of household food insecurity (HFI) on the utilization of maternal healthcare services (MHS) remains unexplored. In this study, we aimed to investigate whether or not household food insecurity was associated with non/inadequate utilization of MHS. Methods: Participants consisted of 3562 mothers aged between 15 and 49 years and with at least one child. The outcome variable was the utilization of MHS, e.g., institutional delivery, attendance ante-, and pre-natal visits. The explanatory variables included various sociodemographic factors (e.g., age, residence, education, wealth) apart from HFI. HFI was measured using the Household Food Insecurity Access Scale (HFIAS). Result: The prevalence of non- and under-utilization of MHS was 5.3 and 36.5, respectively. In the multivariate analysis, HFI, wealth index, and educational level were independently associated with MHS status. The odds of non- and under-utilization of MHS were 3.467 (CI = 1.058-11.354) and 4.104 (CI = 1.794-9.388) times higher, respectively, among women from households reporting severe food insecurity. Conclusion: Severe HFI was significantly associated with both under- and non-utilization of MHS. Interventions programs that address HFI and the empowerment of women can potentially contribute to an increased utilization of MHS.